2007
DOI: 10.1111/j.1475-3588.2007.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Participation Rights: Voicing Opinions in Inpatient Care

Abstract: Children's participation rights, embedded within legislation and policies, are increasingly becoming important in terms of their meaningful implementation in mental health practice. This paper explores ways that adolescents within an inpatient unit voice their opinions, based on participant observation, interviews and the analysis of documents. The voices of patients were encouraged only within the parameters of a specific form, content, time and place. The implications of these findings are discussed in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 14 publications
1
43
0
Order By: Relevance
“…Creating space to allow children and young carers to express themselves is appreciated and may facilitate and build self-esteem. To be sure, it has been suggested that children and young people's participation and partnership working with services leads to increased confidence and self-belief (DfES, 2003;LeFrancois, 2007). What is required is to open up new ways of working and communicating with young people, including young carers, which perhaps would shift the focus from child protection to a new focus on children's voices and rights.…”
Section: R E T R a Cmentioning
confidence: 97%
See 4 more Smart Citations
“…Creating space to allow children and young carers to express themselves is appreciated and may facilitate and build self-esteem. To be sure, it has been suggested that children and young people's participation and partnership working with services leads to increased confidence and self-belief (DfES, 2003;LeFrancois, 2007). What is required is to open up new ways of working and communicating with young people, including young carers, which perhaps would shift the focus from child protection to a new focus on children's voices and rights.…”
Section: R E T R a Cmentioning
confidence: 97%
“…These fears can adversely affect young carers' , parents' and family members' well-being and mental health status over time (Aldridge & Becker, 2003). Young carers feel marginalised by society and by professionals, and this is somewhat compounded by the propensity of services and professionals to instigate child protection responses instead of working closely with young carers in partnership, to give young carers more autonomy, information on coping strategies, a say in the services that are provided for them and a voice (Aldridge & Becker, 2003;LeFrancois, 2007).…”
Section: Fears Of Family Separation and Child Protectionmentioning
confidence: 98%
See 3 more Smart Citations